EVIDENCE OF PERSUASIVE IN PREDICTIVE MURDER - Afriyati, Afriyati; Isnaeni , Belly; Saputra, Agung Arafat (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The teaching on participation as a basis for expanding the criminal penalties for people involved in the realization of a crime. Participation is regulated in Article 55, Article 56 of the Criminal Code and Article 57 of the Criminal Code which means that there are two or more people who commit a crime. Participation (deelneming) in positive law is that there are two or more people who commit a crime or in other words there are two or more people taking part in realizing a crime, it can be stated that a person participates in a relationship with another person (regulated in Article 55 and 56 of the Criminal Code). In Article 55 paragraph 1 to 2 of the Criminal Code, the Concept of Persuasion can be categorized as those who by giving or promising something by abusing power or dignity, with violence, threats or misleading, or by providing opportunities, means or information, intentionally encourage others to commit acts. The participation of the persuader in the crime of premeditated murder is subject to accountability as regulated in Article 340 of the Criminal Code. Article 55 of the Criminal Code contains four forms of participation:a). those who do; b). ordered to do; c). participate in doing; d). persuade/advocate/move other people to do it.